2007
DOI: 10.2337/dc07-1257
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Adiponectin Receptors in Human Visceral and Subcutaneous Adipose Tissue Is Related to Insulin Resistance and Metabolic Parameters and Is Altered in Response to Physical Training

Abstract: OBJECTIVE -Adiponectin receptors 1 and 2 (AdipoR1 and AdipoR2, respectively) mediate the effects of adiponectin on glucose and lipid metabolism in vivo. We examined whether AdipoR1 and/or AdipoR2 mRNA expression in human adipose tissue is fat-depot specific. We also studied whether their expression in visceral and subcutaneous fat depots is associated with metabolic parameters and whether their expression is regulated by intensive physical exercise.RESEARCH DESIGN AND METHODS -We determined metabolic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 26 publications
6
56
0
11
Order By: Relevance
“…29 Euglycaemic-hyperinsulinaemic clamp studies showed that ADIPOR2, but not ADIPOR1 mRNA levels in visceral and subcutaneous AT were correlated with whole-body glucose uptake. 41 In skeletal muscle, the data are less consistent. In non-diabetic Mexicans, lower ADIPOR1/2 mRNA levels in skeletal muscle have been observed in subjects with a family history of type 2 diabetes than in those with no family history of the disease, 42 but ADIPOR1/2 mRNA levels were similar in skeletal muscle of patients with type 2 diabetes and lean controls.…”
Section: Discussionmentioning
confidence: 59%
“…29 Euglycaemic-hyperinsulinaemic clamp studies showed that ADIPOR2, but not ADIPOR1 mRNA levels in visceral and subcutaneous AT were correlated with whole-body glucose uptake. 41 In skeletal muscle, the data are less consistent. In non-diabetic Mexicans, lower ADIPOR1/2 mRNA levels in skeletal muscle have been observed in subjects with a family history of type 2 diabetes than in those with no family history of the disease, 42 but ADIPOR1/2 mRNA levels were similar in skeletal muscle of patients with type 2 diabetes and lean controls.…”
Section: Discussionmentioning
confidence: 59%
“…Four weeks of intensive physical training resulted in increases in skeletal muscle AdipoR1/R2 mRNA expression. The same intervention led to increases in AdipoR1 and AdipoR2 mRNA expression in subcutaneous fat and it was significantly and positively correlated with the increases of AdipoR2 in skeletal muscle 13 .…”
Section: Discussionmentioning
confidence: 79%
“…Although controversial, few studies [10][11][12] have suggested a direct relationship between the levels of adiponectin and physical activity and, as pointed out by Blüher et al 13 , physical training appears to increase the number of adiponectin receptors in subcutaneous fat. However, only a few studies have associated adiponectin plasma levels with objective measures of cardiorespiratory fitness.…”
mentioning
confidence: 99%
“…Adiponectin is negatively correlated with body weight and central adiposity, and its receptors are present in human bone-forming cells, suggesting that adiponectin may link bone and fat metabolism (14). Richards et al (41) found that in nondiabetic women, the increase in adiponectin is associated with a decrease in BMD.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide acts as a satiety signal that stimulates energy expenditure regulating body weight (11), with these actions being modulated by a soluble receptor (12). Physical exercise increases adiponectin levels (13) and the expression of its receptors in muscle (14), and this adipokine may have beneficial effects on the cardiovascular system (15,16).…”
Section: Introductionmentioning
confidence: 99%